Herbicide Resistance in Turfgrass: An Emerging Problem?. (1st August 2013) - Brosnan, J.T.; Breeden, G.K.
Turfgrass is the largest irrigated crop of the continental United States, covering over 16 million hectares, nearly triple that of corn (Zea mays). Although certification programs are in place to limit the presence of weeds in turfgrass seed and vegetative material (i.e., sod, sprigs, etc.), infestations continue to be problematic. Weed infestations in turfgrass and ornamentals have been estimated to impart a 235, 000, 000 negative impact on the United States economy. As a result, herbicides are commonly used to manage weeds of golf course and athletic field turfgrass, sod production fields, as well as residential and commercial lawns. Herbicide resistance has been defined as the inherited ability of a plant to survive and reproduce following exposure to a dose of herbicide normally lethal to the wild type. The development of herbicide resistant weed biotypes is a global problem of agricultural production. Nearly 400 biotypes of herbicide resistant weeds have been reported worldwide, spanning over 200 different plant species. Numerous cases of herbicide resistance have been reported in the United States (142), Australia (61), Canada (58), France (34), Spain (33), and the United Kingdom (24). The rate at which herbicide resistant weeds have developed has increased since the advent of herbicide-tolerant crops in agricultural production systems. This technology allowed for herbicides targeting a single site of action (SOA) to be repeatedly used for effective weed control; thus, reducing the diversity of techniques used for weed management. As a result, selection pressure for herbicide resistant weed biotypes increased. The evolution of herbicide resistant weeds in turfgrass is far less pronounced than in agricultural production systems, in large part due to the fact that genetic traits conferring herbicide tolerance are not used commercially in the turfgrass industry. However, repeated use herbicides targeting similar SOAs for control of problematic weeds has led to the development of herbicide resistant biotypes of annual bluegrass (Poa annua), goosegrass (Eleusine indica), and smooth crabgrass (Digitaria ischaemum) in turfgrass systems. Despite the fact that herbicide resistance in agricultural production has been an issue since 1970, several reports of turfgrass weeds resistant to glyphosate, triazine and triazinones (i.e., simazine, metribuzin), sulfonylureas (i.e., foramsulfuron, trifloxysulfuron), and dinitroanilines (i.e., prodiamine) have surfaced within the past five years. These data illustrate that herbicide resistance is an emerging problem of turfgrass weed management requiring intervention. It has been stated that there is a need to educate agricultural producers regarding the need for diversifying weed management techniques and rotating herbicides targeting different SOAs. Moreover, the researchers suggest that agricultural producers become educated regarding herbicide SOAs and that indiscriminate use of existing herbicides will rapidly increase the evolution of herbicide resistant weeds, thus exhausting the number of herbicide options available for weed management. The hope is that these efforts will curb the rate of resistance development in agricultural production. It is critical that these communication efforts be implemented in turfgrass while the magnitude of herbicide resistance is less pronounced. This article will outline cases of herbicide resistance in turfgrass to further communicate the risks of relying upon herbicides targeting the same SOA for weed management.